If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(w + -4) + 4 = 2(w + 11) Reorder the terms: 7(-4 + w) + 4 = 2(w + 11) (-4 * 7 + w * 7) + 4 = 2(w + 11) (-28 + 7w) + 4 = 2(w + 11) Reorder the terms: -28 + 4 + 7w = 2(w + 11) Combine like terms: -28 + 4 = -24 -24 + 7w = 2(w + 11) Reorder the terms: -24 + 7w = 2(11 + w) -24 + 7w = (11 * 2 + w * 2) -24 + 7w = (22 + 2w) Solving -24 + 7w = 22 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. -24 + 7w + -2w = 22 + 2w + -2w Combine like terms: 7w + -2w = 5w -24 + 5w = 22 + 2w + -2w Combine like terms: 2w + -2w = 0 -24 + 5w = 22 + 0 -24 + 5w = 22 Add '24' to each side of the equation. -24 + 24 + 5w = 22 + 24 Combine like terms: -24 + 24 = 0 0 + 5w = 22 + 24 5w = 22 + 24 Combine like terms: 22 + 24 = 46 5w = 46 Divide each side by '5'. w = 9.2 Simplifying w = 9.2
| 5x-16=x+1 | | 3x-90+x+38= | | 2(1-2z)-3(2z+9)=z-29 | | 3x+9-6+4x=2x-9+4+3+10x | | 72=-8(-4+4r)-2(1+5r) | | 4x^3+16x^2+2x=0 | | 7(6-2(-37))=5(-3(-37)+1) | | 12n-30=-21+9n+2n | | 2(6x+6x+36)=36x | | 7+8p+8p=-8(1-3p)-7(p-1) | | 14m-10=3(4+1m) | | 4x^3+8x^2+2x=0 | | -3(x+1)+19x-9= | | 6=1/5w+7/5w-4 | | m-3m=-14-4m | | x^3=61.81 | | 1.5n-.5=n+3.25 | | -4(2x-2)=-(4x-4) | | Y^3+y^2-16y+16=0 | | -38=4(7+3p)+5(-2-p) | | -6-4x=26 | | 6k-5k+8k-4k= | | -x^3-6=-7 | | 2(5-2z)-2(4z+6)=z-8 | | -2(7k+4)+9=32 | | (-8)x(6)= | | (j-3)j+4+j=196 | | 16x+11x=y | | x^2=16-28 | | 7v+6-3v=2 | | 5x+2=7x-48 | | 5(x+6x)=40(3-4x) |